The madagascan ammonite Neogauthiericeras Collignon, 1969 from the upper cretaceous (Campanian) of Texas - Kennedy, W; Cobban, W (1990)
Neogauthiericeras zafimahovai Collignon, 1969, a basal Campanian marker species in Madagascar is described from the lower Campanian of Texas, USA. It is the first record of the genus outside Madagascar and provides an important biostratigraphic link between the two regions. © 1990 E. Schweizerbart'sche Verlagsbuchhandlung.